2006
DOI: 10.1128/aem.72.2.1445-1451.2006
|View full text |Cite
|
Sign up to set email alerts
|

In Situ and In Vitro Gene Expression by Vibrio vulnificus during Entry into, Persistence within, and Resuscitation from the Viable but Nonculturable State

Abstract: Isolation of Vibrio vulnificus during winter months is difficult due to the entrance of these cells into the viable but nonculturable (VBNC) state. While several studies have investigated in vitro gene expression upon entrance into and persistence within the VBNC state, to our knowledge, no in situ studies have been reported. We incubated clinical and environmental isolates of V. vulnificus in estuarine waters during winter months to monitor the expression of several genes during the VBNC state and compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 51 publications
5
81
1
Order By: Relevance
“…VBNC bacteria are organisms that fail to grow and develop colonies on the media they are normally cultured on, but their metabolic activity capabilities indicate that they are still alive (98). Several reviews of this dormancy state have been published (99,100,101,102,103,104,105,106,107,108), and the list of bacteria known to enter this state is constantly growing. We have also employed diffusion chambers to demonstrate that this phenomenon occurs not only in the lab, but also in situ in estuarine waters (105).…”
Section: Temperature and The Viable But Nonculturable Statementioning
confidence: 99%
“…VBNC bacteria are organisms that fail to grow and develop colonies on the media they are normally cultured on, but their metabolic activity capabilities indicate that they are still alive (98). Several reviews of this dormancy state have been published (99,100,101,102,103,104,105,106,107,108), and the list of bacteria known to enter this state is constantly growing. We have also employed diffusion chambers to demonstrate that this phenomenon occurs not only in the lab, but also in situ in estuarine waters (105).…”
Section: Temperature and The Viable But Nonculturable Statementioning
confidence: 99%
“…VBNC cells lose their viability very quickly as assessed by plate count on agar, while they are able to maintain some metabolic activity or cellular integrity as evaluated using other methods (16,17). Up to now, few studies on viability and activity changes in VBNC V. parahaemolyticus cells have been carried out using alternative methods to standard techniques.…”
mentioning
confidence: 99%
“…Moreover, since some authors have demonstrated the ability of V. parahaemolyticus to ''resuscitate'' from the VBNC state (17,32,33), FCM analyses was used to evaluate physiological and morphological features of the V. parahaemolyticus vegetative form after resuscitation.…”
mentioning
confidence: 99%
“…In this state, bacteria lose their ability to form colonies on culture media (Lleò et al, 1998), but remain alive and capable of producing antigen components (Smith and Oliver, 2006) and virulence factors (Pruzzo et al, 2002). When permissive conditions are restored, VBNC cells may resume cell division (Lleò et al, 2001) and participate in disease transmission and persistence (Xu et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…When bacteria enter the VBNC state, they lose their ability to form colonies on culture media (Lleò et al, 1998), but continue to express antigen components (Smith and Oliver, 2006) and virulence factors (Pruzzo et al, 2002). VBNC bacteria may be able to resume cell division and promote disease transmission and persistence when permissive conditions are restored (Lleò et al, 2001).…”
Section: Introductionmentioning
confidence: 99%